(untitled) (Research, Society and Development, 2021)
Knowing the local climate is a necessary factor for assessing water resources, as several meteorological elements are indispensable throughout the hydrological cycle. In this context, the objectives of this work are to estimate the maximum, minimum and annual evapotranspirations for the hydrographic basin of the Uruçuí Preto River, state of Piauí. The estimate of the minimum, maximum and annual evapotranspiration was made from the empirical equations for the estimation of the air temperature for the area of the basin under study. Historical series of monthly air temperature values were used, from uniform periods with 30 years of observations, for the 49 municipalities that encompass the study area. With the data from these series, equations were adjusted by the least squares method, obtaining multiple linear regression equations and tested the statistical method. With the average air temperature data estimated, evapotranspiration was estimated using the empirical method of Thornthwaite. Values for the average air temperature were estimated, estimated by the Estima_T software. The average evapotranspiration oscillation in the studied area occurs between 92.4 mm in February and 170.1 mm in October. Maximum evapotranspiration ranges from 111.3 to 202.8 mm. The minimum ETP ranges from 70.7 to 130.2 mm. The ETP estimates of the Uruçuí Preto - Piauí river basin are dependent on geographic positioning (latitude and longitude), and also on local orography. In average terms, the occurrence classes of 70 to 125 mm, 125 to 175 mm and the highest class above 200 mm stand out, which together make up 84.4% of the study area, representing a variation of 5.3 mm to 10.8 mm, in terms of average daily evapotranspiration, in practically the entire basin.